ANALISA DAYA SERAP SILIKA GEL BERBAHAN DASAR ABU SEKAM PADI - Fahmi, Hendriwan; Nurfalah, Abdul Latif (Jurnal Ipteks Terapan, 2016)
Rice husk ash Silica Gel is aproduct which call be used in preventing the humidity by absorbing the water ion on the water andonthe air. This absorbing isbased onthe size, the composition and the total amount ofpolluter which contained on the Silica Gel. The purpose of making this silica gel is to seehow much thiskind of Silica Gel can absorb and compare it to the synthetic one,and also processing rise husk ashto be something useful, Ion water can be absorbed much more by using this natural silica gel if it is compared to the synthetic silica gel. This is because of its capable inabsorbing more âOHand O from water and air. Afterdoing a research with column method, silica gel was beingput in 50 ml water. Fromthis research, natural silica can absorb much more water (0.0010 gr/ml), 0.285 % water level ofweigh in comparing with synthetic one (0.008gr/ml) with 0.248 %water level ofweight andsintering (0,007 gr/ml) 0.253%water level and non-sintering silica gel contains 39.22 % weight of silica, 30.93 %weight of sintering silica gel, and 33.40 % of the synthetic. More silica and water level, means more total amount of absorbing. This silica gel application is considered with capability ofabsorbing andthe level of the water.